PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA TERHADAP KEINGINAN BERPINDAH TEMPAT KERJA MELALUI KEJENUHAN (BURNOUT) TENAGA KEPENDIDIKAN KONTRAK KERJA UNIVERSITAS JEMBER - Nur Dwiyanto; Raden Andi Sularso (STIE Mandala Jember, 2017)
Jember University (UNEJ) is a State University (PTN) that has the main duty of providing higher education and provide education based on Indonesian culture in a scientific way that includes education, research and community service to develop skills and improve the quality of life and human dignity of Indonesia in efforts to achieve the national goal. But to achieve its goals are still having some problems where the level of burnout and the turnover intention, especially the temporary educational employees is still quite high. The goals of research are: to prove significantly the direct influence of leadership style, work environment to turnover intention nor the indirect influence of leadership style, work environment to turnover intention through the burnout. This research is a kind of explanatory research with quantitative approach by sampel as much as 245 respondent is the temporary educational employees Jember University. For analyzing variable causal relationship and hypotesis test, so analyse tools which use is Structural Equation Modeling (SEM).Based of Structural Equation Modeling (SEM) result known that the leadership style have positive and significant to burnout; work environment have positive and significant to burnout; leadership style have positive and significant to turnover intention; work environment have positive and significant to turnover intention; burnout have positive and significant to turnover intention.